2021
DOI: 10.1097/gox.0000000000003745
|View full text |Cite
|
Sign up to set email alerts
|

Do We Need Support in Prepectoral Breast Reconstruction? Comparing Outcomes with and without ADM

Abstract: Background: The majority of two-stage prepectoral breast reconstruction has been described utilizing acellular dermal matrix (ADM). Although reports of prepectoral breast reconstruction without ADM exist, there is a paucity of comparative studies. Methods: A single-institution retrospective review was performed of consecutive patients undergoing immediate prepectoral two-stage breast reconstruction with tissue expanders from 2017 to 2019. Short-term rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…When comparing our institution’s outcomes, we found that prepectoral tissue expander reconstruction had no statistically significant differences in total complication rates, major complication rates, infections rates, or explant rates in comparison with historical subpectoral reconstructions with the use of ADM. In addition, our reported complication profile and explant rates were comparable with recent literature’s reported outcomes 11,12,14,25 . Our experience suggests that the tissue expander phase of prepectoral breast reconstruction can be performed with a similar complication profile seen in patients who underwent subpectoral breast reconstruction with ADM.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…When comparing our institution’s outcomes, we found that prepectoral tissue expander reconstruction had no statistically significant differences in total complication rates, major complication rates, infections rates, or explant rates in comparison with historical subpectoral reconstructions with the use of ADM. In addition, our reported complication profile and explant rates were comparable with recent literature’s reported outcomes 11,12,14,25 . Our experience suggests that the tissue expander phase of prepectoral breast reconstruction can be performed with a similar complication profile seen in patients who underwent subpectoral breast reconstruction with ADM.…”
Section: Discussionsupporting
confidence: 84%
“…A number of surgeons perform prepectoral reconstruction with the use of ADM citing either improved prosthetic position control or additional soft tissue coverage in the event of skin compromise 24 . However, design modifications to tissue expanders, such as the fixation tabs, now allow surgeons to secure expanders in place without the need for ADM 12–14 . Furthermore, in the event flap necrosis with exposed unincorporated ADM, most surgeons operatively revise just as they would with exposed prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the authors comment that ADM has "enabled prepectoral breast reconstruction," implying that the procedure cannot feasibly be performed without ADM. Yet, several surgeons have reported reassuring results in patients without ADM. [4][5][6][7][8] We had previously performed a systematic review of the literature on all reported prepectoral patients undergoing reconstruction with and without ADM and identified no significant differences in complication rates. 9 In addition, several publications have identified possible safety concerns with the use of ADM in submuscular reconstruction.…”
mentioning
confidence: 99%
“…Unfortunately, few studies have compared prepectoral reconstruction with and without ADM in a head-to-head manner and lack sufficient size for adequate statistical power to determine true differences. 19,20 The aim of this study was to obtain a preliminary understanding of early complication rates (within 90 days) between patients who underwent prepectoral TE placement with and without ADM. The hypothesis is that the absence of ADM would not change rates of explantation and overall short-term complications.…”
mentioning
confidence: 99%